Neurotrophic factors as double-edged swords in osteosarcoma: drivers of tumour growth and immune remodelling - Lei, Puzhou; Li, Lei (Frontiers in Immunology, 2025)
Neurotrophic factors, once considered exclusive guardians of neuronal integrity, are increasingly recognised as pivotal regulators of osteosarcoma biology. Their paradoxical enhancement of malignant fitness and an immunosuppressive microenvironment complicates therapy, with metastatic survival remaining stubbornly low. Recent mechanistic studies reveal that ligand-dependent NGF–TrkA, BDNF–TrkB and GDNF–RET circuits intersect with MEK/ERK, PI3K/AKT and STAT3 pathways to ignite proliferation, invasion and metastatic spread. Concurrently, neurotrophin signalling recalibrates macrophage polarity, dampens cytotoxic T-cell function and orchestrates neural-immune feedback loops that shield tumours from surveillance. Harnessing this duality demands an integrative strategy. We synthesise tumour-intrinsic and extrinsic neurotrophic axes, delineate neuro-immune crosstalk, and highlight interventions—TRK/RET inhibitors, CSF1R blockade, β-adrenergic antagonists—aimed at converting this liability into therapeutic leverage. By framing neurotrophic factors as double-edged swords, this review provides a conceptual and practical roadmap for exploiting their vulnerabilities to improve outcomes in osteosarcoma.